Numerical simulation of various PCM container configurations for solar dryer application - Manikandan, Saranya; Muthuvairavan, Guna; Samykano, Mahendran; Natarajan, Sendhil Kumar (Elsevier Ltd, 2024)
In the context of solar dryers, where drying time is constrained by available sunshine hours and excessive heat during these periods can potentially lead to mineral loss in food, the incorporation of phase change material (PCM) for thermal energy storage emerges as a viable solution. However, the response time of PCMs plays a major role in its charging and discharging in solar dryer performance, prompting extensive research into PCM container configurations to reduce this limitation. Investigations have been conducted through numerical simulations and experimental studies to explore various configurations of PCM. In this study, four distinct container configurations were employed, alongside the introduction of fins, with two variations: solid and hollow. In this regard, Paraffin RT58, with its melting point closely aligned with the operating temperature of the solar dryer, is considered a suitable choice in simulation using ANSYS Fluent. The simulation results revealed that the horizontal rectangles demonstrate the quickest rates for melting and solidification, whereas the cylindrical shape exhibits the most extended durations for these processes. The introduction of fins has a notable impact on reducing both melting and solidification times, with a further decrease observed as the number of fins increases. While solid fins provide slightly superior reductions in melting and solidification times, opting for hollow fins presents benefits in terms of material efficiency, weight reduction, and cost savings.